Flexible all-in-one zinc-ion batteries. Issue 38 (20th September 2019) - Zhang, Yan; Wang, Qingrong; Bi, Songshan; Yao, Minjie; Wan, Fang; Niu, Zhiqiang
Abstract : Flexible all-in-one ZIBs exhibit excellent physical flexibility and stable electrochemical performance under different mechanical deformations. Abstract : The recent development of flexible and wearable electronic devices has increased the demand for energy storage devices with excellent flexibility and structural stability. Aqueous zinc-ion batteries (ZIBs) are promising energy storage devices due to their low cost, high safety, and eco-friendliness. Therefore, flexible ZIBs have to be considered. Herein, we design the flexible all-in-one ZIBs, where the reduced graphene oxide/polyaniline (rGO/PANI) cathode, cellulose nanofiber (CNF) separator, and exfoliated graphene (EG)/Zn anode are integrated together using an all-freeze-casting strategy. The continuous seamless connection of such all-in-one ZIBs can avoid displacing and detaching between the electrodes and separator under different bending states and improve the load-transfer capacity and interface strength between the neighboring component layers. As a result, the all-in-one ZIBs show excellent flexibility and superior electrochemical stability under different bending states.